HUBUNGAN SELF CARE DIABETES DENGAN KUALITAS HIDUP PASIEN DM TIPE 2 DI POLIKLINIK INTERNA - Putu Inge Ruth Suantika (Coping: Community of Publishing in Nursing, 2015)
Diabetic type 2  is a metabolic disease which has clinical manifestation inadequate insulin.  Patient diabetic type 2  needs to perform diabetic self-care as one of the handlers of diabetic. Diabetic self-care has 4 domains, such as diet, exercise, blood sugar control, foot care and treatment. When patient diabetic type 2 were able to perform self-care of diabetes, it has an impact on the quality of life that includes four domains such as physical health, psychological, social relationship, and environment. The purpose of this study was determined the relationship of diabetic self-care with quality of life of patients diabetic type 2 at Internal Out of Ward of Badung Hospital. The study used a correlation study design using cross sectional approach. Sampling used purposive sampling technique. Normality test used is the Kolmogorov-Smirnov. Correlation test used product moment (p<0,05). The result of this study, there was significant of variable. Correlation test with product moment (p<0,05), which was showed by p=0,000 and r=0,601. The conclusion of this study,  there was significant relations between self care and quality of life of patient diabetic type 2 with r value 0,601 and p value 0,000. The contribution of self care was 0,361. It means self care had correlation 36% with quality of life. There was another factors which can had correlation with quality of life.